Pengaruh Kecerdasan Emosional Dan Self Compassion Terhadap Stress Tolerance Pada Warga Binaan Sosial (Wbs) Wanita Di Panti Sosial Perlindungan Bina Karya Harapan Mulia - Diana Sari, Rizma; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research aims to determine emotional intelligence and self-compassion regarding stress tolerance in social assistance residents (WBS) women at the Bina Karya Harapan Mulia Protection Social Home. This research is a quantitative research with a population of residents assisted by social institutions. The sample used was 106 residents assisted by social institutions. The data collection method uses a scale of stress tolerance, emotional intelligence, and self-compassion. The data collection system uses techniques and the data collection process is carried out by paper questionnaires. Normality test uses Kolmogorov- Smirnov and hypothesis testing uses multiple linear analysis. The normality test on the stress tolerance scale had a significance value of 0.946 (p > 0.05), the emotional intelligence scale had a significance value of 0.213 (p > 0.05), the self compassion scale had a significance value of 0.517 (p > 0.05).Based on the results of research on the emotional intelligence scale, a probability value of sig. p = < 0.001 (p < 0.05); r = 0.407; R2 = 0.166 so that H1 proposed is accepted, namely that there is a positive and significant influence between emotional intelligence and stress tolerance in social assistance residents (WBS) women in the Bina Karya Harapan Mulia protection social institution. On the self-compassion scale, a probability value of sig is obtained. p = 0.018 (p < 0.05); r : 0.230; R2 = 0.053 so that the proposed H2 is accepted, namely that there is a positive and significant influence between self- compassion on stress tolerance in social assistance residents (WBS) women in the Bina Karya Harapan Mulia protection social institution. On the emotional intelligence and self-compassion scale, a probability sig value was obtained. p = < 0.001 p (< 0.05); F = 15.754 with R2 = 0.234 so that H3 proposed is accepted, namely that there is a positive and significant influence between emotional intelligence and self-compassion on stress tolerance in social assistance residents (WBS) women in the Bina Karya Harapan Mulia protection social institution.